The Dynamics of Asymmetric Conflicts:: The Israeli-Palestinian Case - Gallo, Giorgio; Marzano, Arturo (Journal of Conflict Studies, 2009)
ABSTRACT Asymmetry is considered one of the most relevant features in today’s conflicts. In this article we address one particular type of asymmetry — structural asymmetry. After introducing the main characteristics and different phases of these types of conflicts, i.e. conscientization, confrontation, negotiation, and sustainable peace, we address the specificity of the Israeli-Palestinian case presented here as a typical case of a structurally asymmetric conflict. The aim is to explain why, despite the many negotiation phases this conflict has been through, none has ever led to a sustainable peace. On the contrary, each negotiation has brought on yet another confrontation phase, in a never-ending series of loops. The strong imbalance between the two sides and the scarce reciprocal conflict awareness represent the two main reasons for explaining this pattern.